DAS TEIAS DE ANANSE PARA O MUNDO – ÁFRICAS E AFRICANIDADES NA LITERATURA INFANTIL E JUVENIL CONTEMPORÂNEA EM LÍNGUA ESPANHOLA - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
The reflections I bring in this dissertation aim to identify the traits of Africanities in children's and young people's literature in the Spanish language in its Afro-Diasporic context. To present such traits of Africanities, I had to rethink how the African matrix appears in Spanish-language short stories and in what they consist. For this, I listened in the form of categories of analysis, the found africanities. Being these categories: The representations of Ananse; The power and importance of the word for African cultures; Áfricas: memory and community; The presence of animals / characters. With regard to theoretical and methodological development, I start from the recognition of the classical studies that approach the theme of children's and youth literature during the historical trajectory of this literary genre. Such as: Támes (1990); Coelho (2000, 2006); Hunt (2010), among others. However, I focus mainly on the issues regarding the representation of the black characters, the research of Rosenberg (1985); Oliveira (2003, 2010); Gouvêa (2005); Jovino (2006); Araujo (2010, 2015); Debus (2012); among others. With regard to the theoretical elucidation of the concepts of africanities and afrocentricity, which are the guiding axes of this research, it was necessary to carry out reflective studies by discussing them with postulations of Afro-Brazilian and African researchers. Already, for the methodology of analysis of short stories, I’m based on the African praxis, postulated by Silva (2008). I’m also explain that the analysis will be done in an afro centered perspective, prioritizing Afro-diasporic theoretical basis. Regarding the corpus of this study, the works chosen were: Anancy in Limón (2002), Costa Rica and Multiculturality and Plurilingualism - Oral Tradition and multilingual education in Central and Southern Africa (2012), from Equatorial Guinea. The results point out that the researches with children and young people's literature that discuss the representation of black characters, although there are still some vestige of stereotypes, as highlighted by Rosemberg (1985), Oliveira (2003, 2010), Araujo (2010, 2015 )). It is worth emphasizing the didactic and pedagogical character of the narratives and the importance of the argumentation, articulation, developed by Ananse, the power of the word, animals and memory and community for African cultures.
Keywords: Literatura infantil e juvenil; Contos; Africanidades; Afrocentricidade; Língua e literaturas em língua espanhola; Children and youth literature; Tales; Africanities; Language and literature in Spanish; Afrocentricity; CNPQ::LINGUISTICA, LETRAS E ARTES::LETRAS